MEMBANGUN SINERGI ANTARA KESEJAHTERAAN FORMAL DAN INFORMAL (SUATU KAJIAN ATAS TANTANGAN DAN KELEBIHAN) - N’CONO, MUHAMMAD WASRIK (GANEC SWARA, 2023)
Welfare is a fundamental right of every individual. However, access to this right can vary depending on the context and culture of society. Formal welfare guaranteed by the state through laws and formal institutions such as government agencies often fails to reach the population evenly, especially in rural areas and small towns. On the other hand, informal welfare, which relies on social relationships, kinship, and community trust, can be an alternative for those who struggle to access formal welfare. However, informal welfare also has its weaknesses and may not fully meet individual needs. Therefore, this paper attempts to discuss the differences between formal and informal welfare in terms of access and societal practices. Research findings indicate that formal welfare has weaknesses such as difficulties in addressing all of society's needs and inflexibility in dealing with complex issues, unlike informal welfare, which offers more flexibility and adaptability. Thus, there is a need for synergy between formal and informal welfare, which can be achieved through various means. Firstly, by enhancing access and community involvement in formal welfare programs. Secondly, by recognizing and leveraging the potential of informal welfare. Thirdly, by integrating formal and informal welfare into development policies. This integration can enhance the effectiveness and efficiency of development programs and help address uncertainties, access inequalities, and limitations in resource capacity and quality